Comparative evaluation of salivary pH and buffering capacity of commonly available flavoured drinks in India - Awasthi, Neha; Singh, Sukhdeep; Grover, Nikhil (International Journal of Psychosocial Rehabilitation, 2020)
Background & objectives: There is a general perception amongst consumers that fruit flavoured drinks are essentially water with subtle flavoring. As a consequence, they are perceived as being dentally safe. However, these drinks come with a drawback as far as oral health is concerned. An increased consumption of flavoured drinks such as soft drinks, sports drinks and fruit juices is becoming noteworthy because of concern for dental erosion. The objective of this study was to measure the buffering capacity of the drinks used, and evaluate pH of saliva after intake of various flavored drinks at different time intervals. Materials and methods: The present study included 30 subjects, 15 male and 15 female, with the mean age group of 7±1.2 years. Five flavoured drinks were used in this study, to measure the salivary pH after consumption of the drinks, and to assess the buffering capacity of each drink. The drinks used were; apple juice, Appyfizz, milk based drink, Pepsi and Gatorade. Buffering capacity of each drink was estimated by titration with sodium hydroxide. The results were tabulated and analysed statistically. Results: Significant fall in the salivary pH was recorded for Pepsi and Gatorade groups, while the milk based drink maintained the pH of the saliva to the resting value. Therefore, milk based drinks are a safer option as compared to soft drinks, and sports drinks.